Circulating Metabolites of the Human Immunodeficiency Virus Protease Inhibitor Nelfinavir in Humans: Structural Identification, Levels in Plasma, and Antiviral Activities - Zhang, Kanyin E. (American Society for Microbiology, 2001)
Nelfinavir mesylate (Viracept, formally AG1343) is a potent and orally bioavailable human immunodeficiency virus (HIV) type 1 (HIV-1) protease inhibitor (K(i) = 2 nM) and is being widely prescribed in combination with HIV reverse transcriptase inhibitors for the treatment of HIV infection. The current studies evaluated the presence of metabolites circulating in plasma following the oral administration of nelfinavir to healthy volunteers and HIV-infected patients, as well as the levels in plasma and antiviral activities of these metabolites. The results showed that the parent drug was the major circulating chemical species, followed in decreasing abundance by its hydroxy-t-butylamide metabolite (M8) and 3′-methoxy-4′-hydroxynelfinavir (M1). Antiviral assays with HIV-1 strain RF-infected CEM-SS cells showed that the 50% effective concentrations (EC(50)) of nelfinavir, M8, and M1 were 30, 34, and 151 nM, respectively, and that the corresponding EC(50) against another HIV-1 strain, IIIB, in MT-2 cells were 60, 86, and 653 nM. Therefore, apparently similar in vitro antiviral activities were demonstrated for nelfinavir and M8, whereas an approximately 5- to 11-fold-lower level of antiviral activity was observed for M1. The active metabolite, M8, showed a degree of binding to human plasma proteins similar to that of nelfinavir (ca. 98%). Concentrations in plasma of nelfinavir and its metabolites in 10 HIV-positive patients receiving nelfinavir therapy (750 mg three times per day) were determined by a liquid chromatography tandem mass spectrometry assay. At steady state (day 28), the mean plasma nelfinavir concentrations ranged from 1.73 to 4.96 μM and the M8 concentrations ranged from 0.55 to 1.96 μM, whereas the M1 concentrations were low and ranged from 0.09 to 0.19 μM. In conclusion, the findings from the current studies suggest that, in humans, nelfinavir forms an active metabolite circulating at appreciable levels in plasma. The active metabolite M8 may account for some of the antiviral activity associated with nelfinavir in the treatment of HIV disease.